The knowledge translation toolkit : bridging the know-do gap : a resource for researchers - Bennett, Gavin; Jessani, Nasreen (New Delhi, India : SAGE Publications, 2011)
'The Knowledge Translation Toolkit provides a thorough overview of what knowledge translation (KT) is and how to use it most effectively to bridge the'know-do' gap between research, policy, practice, and people. It presents the theories, tools, and strategies required to encourage and enable evidence-informed decision-making. This toolkit builds upon extensive research into the principles and skills of KT: its theory and literature, its evolution, strategies, and challenges. The book covers an array of crucial KTenablers--from context mapping to evaluative thinking--supported by practical examples, implementation guides, and references. Drawing from the experience of specialists in relevant disciplines around the world, The Knowledge Translation Toolkit aims to enhance the capacity and motivation of researchers to use KT and to use it well'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Research -- Methodology; Knowledge management; Evaluation; Communication in science; Research -- Social aspects